UNDERSTANDING THE DYNAMICS OF THE UPTAKE OF MATERNAL HEALTH SERVICES IN KEBBI STATE USING A SYSTEMS THINKING APPROACH - Asta, Musa; Fonkam, Mathias; Danjuma, Nehemiah; Kaoje, Abubakar Dan; Muhammad, Abubakar (International Journal of Research -GRANTHAALAYAH, 2020)
This study focused on the dynamics of Maternal Health Services utilization in Kebbi State using a Systems Thinking approach. The broad objective was to understand the effect of interventions intended to promote utilization of Maternal Health Services. The study evolved a model to represent the causal interrelationship, interdependencies and feedback influences of the multifactorial and multisectoral public health approach on utilization of public maternal health services using a Systems Thinking approach. This enabled us draw inferences on the effect on the mother, the intended end-beneficiary from these interventions. Using a Causal Loop Diagram, we were able to identify reinforcing and balancing feedback loops that could explain the behavior or outcomes being observed. The findings revealed that the feedback in the system is driven by limited resources at the household levels, technical quality of health care services, and knowledgeableness of women on maternal health services. From this, we were able to recommend that policy-makers should try to effectively address socio-economic inadequacies at the household level including socio-cultural practices leading to low level of girl-child school enrolment, and several factors affecting motivation of health care workers. While efforts to ensure quality of care and community awareness should be maintained, emphasis and priority needs to be given to interventions that target economic improvements of households.